2006
DOI: 10.1007/s00125-006-0270-z
|View full text |Cite
|
Sign up to set email alerts
|

Common polymorphisms of calpain-10 are associated with abdominal obesity in subjects at high risk of type 2 diabetes

Abstract: Aims/hypothesis: The mechanisms by which the calpain-10 gene (CAPN10) affects the risk of type 2 diabetes are unclear. Therefore, we investigated the effects of four polymorphisms in CAPN10 (single nucleotide polymorphism [SNP]-43, SNP-44, Insertion/Deletion [Indel]-19 and SNP-63) on insulin secretion, insulin action and abdominal fat distribution in offspring of patients with type 2 diabetes. Subjects and methods: Insulin secretion was determined by an IVGTT, insulin action by the hyperinsulinaemic-euglycaemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
1
10
0
1
Order By: Relevance
“…Most previous studies on Calpain-10 did not find a genderspecific effect of this gene on metabolic parameters. On the other hand, a previous study including offspring of patients with T2DM showed that SNP-43, but not SNP-19 or -44, was associated with the intra-abdominal fat area in men and the authors suggested that Calpain-10 may increase the risk of T2DM via affecting abdominal obesity in men with high risk for T2DM [31]. Therefore, the relationship between Calpain-10 and increased BMI in men presented in our study needs to be investigated extensively.…”
Section: Prace Oryginalnementioning
confidence: 96%
“…Most previous studies on Calpain-10 did not find a genderspecific effect of this gene on metabolic parameters. On the other hand, a previous study including offspring of patients with T2DM showed that SNP-43, but not SNP-19 or -44, was associated with the intra-abdominal fat area in men and the authors suggested that Calpain-10 may increase the risk of T2DM via affecting abdominal obesity in men with high risk for T2DM [31]. Therefore, the relationship between Calpain-10 and increased BMI in men presented in our study needs to be investigated extensively.…”
Section: Prace Oryginalnementioning
confidence: 96%
“…Similar to other calpains, CAPN10 consists of an isoform-specific large subunit and a common small subunit, and was shown to function as intracellular calcium-dependent cysteine proteases in calcium-regulated signaling pathways [5]. CAPN10 is expressed at the mRNA and protein levels by several tissue types, with different mRNA isoforms reported, in particular those involved in the regulation of glucose homeostasis, such as pancreatic β islet cells, liver, skeletal muscle, and adipocytes [6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…Several case control and association studies indicated that polymorphisms in CAPN10 are associated with the development of T2D and insulin resistance, more so in obese patients with an earlier age of disease onset [6,8-10]. These include the at-risk UCSNP-43 G/A variant located in the third intron, UCSNP-19 2R (two 32-bp repeats)/3R (three 32-bp repeats) present in intron 6, and UCSNP-63 C/T variant within CAPN10 intron 13 [7,10]. This contribution of the CAPN10 variants to T2D pathogenesis was highlighted by the findings that select UCSNP-43/UCSNP-19/UCSNP -63 haplotypes (112 and 121) were associated with heightened risk of T2D in select ethnic groups, and as at-risk dipolotypes (haplotype combinations) were reported for many populations [10-13].…”
Section: Introductionmentioning
confidence: 99%
“…Second, we investigated ten polymorphisms in nine genes (ADRB1, ADRB2, ADRB3, CAPN10, IRS1, UCP2, PPARGC1A, PTPN1 and ENPP1), each of which has been associated with at least two components contributing to the metabolic syndrome [19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%